Social security wealth and early retirement in public pension scheme - Haris, Asmaddy; Said, Rusmawati (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
The main objective of this study is to investigate the decision of workers to opt for early retirement. The study focuses on the public sector pension scheme. The simulation technique is used to calculate the social security benefit at two different ages; compulsory retirement age and early retirement age. Data gained from the simulation process represent two main social security variables, namely the social security wealth and social security accrual. Then, both variables will be estimated together with other explanatory variables such as marital status, sex, education level, experience and age using logistic method to examine its relationship with early retirement decision. The results show that the substitution effect of public sector pension scheme is more dominant than income effect. The findings of this study concludes; public sector pension scheme fails to encourage public workers to settle for early retirement and thus it is not capable of becoming a policy instrument to downsize the public sector work force and unable to create job vacancies.